Life Cycle Analysis of Ponggok Tourism Village, Polanharjo District, Klaten Regency, Central Java Province - Aji, Khusnul Bayu; Kusumawanto, Arif (Journal of Indonesian Tourism and Development Studies, 2020)
This study aims at analyzing the development of Ponggok Tourism Village since its first progression as a tourism destination. Ponggok is one of the best tourism villages in Indonesia according to the 2017 report published by the Ministry of Villagers, Disadvantaged Regions and Transmigrations. However, the tourism village tends to be in a stagnant condition and even experience a decline in visitors. The life cycle analysis is chosen as the approach to fulfill the requirements needed to study the time series (longitudinal) data to dissect the development of Ponggok Tourism Village. The indicator and parameter of assessment in this life cycle analysis is the model stated by Laurenço: planning, action, and living. The technique of primary data collecting is through observation, mapping, interview, and Focus Group Discussion (FGD). Furthermore, the secondary data is acquired through literature studies and institutional surveys in accordance with the scope of the study. The result of the research shows that the development of Ponggok Tourism Village has, at least, four segments of time. The first segment occurred in 2007-2010, the second segment occurred in 2011-2013, the third segment was 2014-2016, and the fourth segment of time occurred in 2017-2018. In the aftermath of this study's results, it is recommended that Ponggok Tourism Village need to replan their strategies to avoid the stagnation-decline stage and to stimulate the occurrence of rejuvenation.  Keywords: Life Cycle Analysis, Ponggok, Tourism Village.